Urinary tract trauma as a predictor of acute kidney injury in severely injured patients: A retrospective analysis of observational studies - Frelich, Michal; Pavlicek, Jan; Bursa, Filip; Vodicka, Vojtech; Salounova, Dana; Sklienka, Peter (Biomedical papers, 2024)
Aim. The main objective of this study was to determine whether urinary trauma increases the risk of acute kidney injury (AKI) in patients with severe trauma. As a secondary objective, we assessed the reliability of neutrophil gelatinase-associated lipocalin (NGAL) in the early prediction of AKI in this patient population.Methods. Retrospective analysis of two prospective observational studies involving 179 adult patients with severe trauma (Injury Severity Score >16). NGAL levels were measured by taking a blood sample 24 h after admission. AKI was diagnosed according to the Kidney Disease Improving Global Outcomes (KDIGO) classification.Results. The overall incidence of AKI was 29%. Kidney or vascular injury was an independent risk factor for AKI (risk ratio [RR] = 3.1, 95% confidence interval [CI] 1.93-4.90). Trauma to urinary passages was also associated with an increased risk of AKI (RR = 4.2, 95% CI 2.70-6.46). Among patients without urinary tract injury, serum NGAL levels were significantly higher in trauma patients who developed AKI during the first 5 days in the intensive care unit (ICU) compared to patients without this organ dysfunction (214.6 ug/L [IQR 167.3] vs. 90.6 ug/L [IQR 58.4]; P<0.001). In patients with urinary tract trauma, there was no difference in the NGAL levels between the two groups (184.6 ug/L [IQR 139.9] vs. 118.3 ug/L [IQR 118.1]; P=0.216). NGAL was not a reliable predictor of AKI in patients with urinary trauma (AUC 0.660).Conclusion. Urinary tract injury is associated with a significant increase in AKI in patients with severe trauma during the first 5 days of hospitalization in the intensive care unit. In these patients, NGAL is not a reliable predictor of the development of AKI.
Keywords: acute kindey injury; severe trauma; NGAL